Presenting a Model of Managerial practical wisdom in Hospitals - Mahdavi Akramsadat; Ardabili Farzad Sattari; Kheirandish Mohammad; Ebrahimpour Habib; Daryani Shahram Mirzaei (Management)
This qualitative study was conducted to provide a model of managerial practical wisdom in public hospitals in order to define the components affecting managerial practical wisdom, development strategies and its results in hospitals based on interpretive paradigm using Grounded strategy and content analysis technique and based on paradigm model of Corbin and Strauss (2008). To this end, semi-structured interviews were conducted with 21 hospital managers, professors and experts in the field of health care management. The basic themes of the interviews during the data analysis and coding stage identify the central class, causal, contextual, intervening factors, strategies and consequences of managerial practical wisdom in the form of a paradigm model and finally to create Grounded theory about managerial practical wisdom in these hospitals. Accordingly, the dimensions and components of practical wisdom among the managers of the mentioned hospitals were cognitive abilities and managerial competencies, factors affecting its development including individual factors (personal experiences, personality pattern, and individual values) and organizational factors (spirituality at work, organizational values and organizational will).Moreover, the results of developing this type of wisdom among the mentioned managers can be categorized as individual results (mental and psychological well-being), organizational results (improving service quality, stakeholder satisfaction, organizational dynamism and agility, organizational vitality and organizational citizenship behaviors) and social outcomes (social capital development). These results can be used in the creation and development of quantitative tools for measuring managerial practical wisdom and as a qualitative complement in evaluating the quality of decisions among hospital managers.